2019
DOI: 10.1038/s41598-019-43415-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanism of “Rare Earth” texture evolution in a lean Mg–Zn–Ca alloy

Abstract: The entire recrystallisation sequence and associated crystallographic texture evolution of Mg-0.8Zn-0.2Ca (wt.%) alloy was tracked using a quasi-in-situ electron backscatter diffraction (EBSD) method. Characteristic “Rare Earth” (RE) texture was formed, originating mainly from double twins and twinning-related shear bands consisting of compression and double twins. The RE textures appeared during the nucleation stage and were preserved during the relative uniform grain growth period beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Ternary additions of alkaline earth elements such as Ca and Sr lead to a weakened basal texture. [193][194][195] The effect of a small amount of Ca on microstructure and its evolution is also shown in Figure 41. [193] For the purpose of comparison, the ternary alloy, Mg-0.8Zn-0.16Ca (wt pct), was produced under similar processing conditions.…”
Section: B Plastic Deformation Of Rolled Plates and Sheetsmentioning
confidence: 95%
“…Ternary additions of alkaline earth elements such as Ca and Sr lead to a weakened basal texture. [193][194][195] The effect of a small amount of Ca on microstructure and its evolution is also shown in Figure 41. [193] For the purpose of comparison, the ternary alloy, Mg-0.8Zn-0.16Ca (wt pct), was produced under similar processing conditions.…”
Section: B Plastic Deformation Of Rolled Plates and Sheetsmentioning
confidence: 95%
“…During deformation at a higher temperature, recrystallization and twinning are active concurrently. In this case, twins can be a nucleus for the recrystallization process (Basu andAl-Samman, 2015, 2017;Guan et al, 2019). In Mg-LPSO alloys a particle-stimulated nucleation (PSN) process can control the recrystallization process (Oñorbe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…RE elements are expensive, and therefore, it is desirable to find alloy compositions that can perform at least to the same level as those involving REs. Calcium is the best economic alloying element that can compete with the good-for-all-illnesses-of-Mg, the RE elements, as it seems to provide remedies for a number of shortcomings and anomalies of Mg alloys Guan et al, 2019). Furthermore, it has been shown that Ca addition conferred arguably the most attractive property to Mg, that is, protection of the melt against atmospheric corrosion, eliminating the need for a protective gas cover (Kim, 2011) during secondary melting.…”
Section: A Competitor To Rare Earth Elements? Calcium Containing Alloysmentioning
confidence: 99%